Neural Correlates of Performance Monitoring During the Transition to Young Adulthood. Issue 2 (25th May 2016) - Knežević, Martina; Veroude, Kim; Jolles, Jelle; Krabbendam, Lydia
ABSTRACT: Cognitive challenges during transition to adulthood are generally high and require particular skills, such as self‐control, performance evaluation, and behavioral adjustment for success in everyday living. However, age and sex differences in timing and efficiency of brain maturational processes in the early twenties are not well known. We used a go/no‐go paradigm and fMRI to focus on the neural processes underlying response inhibition and performance monitoring during the transition from late adolescence (aged 18–19) to young adulthood (aged 23–25). During performance monitoring, late adolescents showed more activation in right inferior frontal gyrus than young adults, while males showed more activation in left inferior parietal lobe than females. No effects of age and sex were found for response inhibition. Our findings suggest that age and sex‐related differences in neural basis of performance monitoring continue to change between late adolescence and young adulthood.